Некоторые морфо-физиологические и биохимические изменения у млекопитающих, вызванные действием инсектицидов в условиях эксперимента - Федоренко, А.П.; Антипчук, Ю.П.; Рогатко, И.В. (Вестник зоологии, 1971)
Investigations were carried out with M. arvalis Pallas , M. socialis Palla s and rabbits. The effect of DDT, hexachlorane and chlorophos in doses applied in practice was studied. It was established that these insecticides evoke pathological and anatomical changes in viscera of the animals under study, disturbs the blood and respiration pictures, cardiac rhythm, cause displacements in the blood protein picture. Morpho-physiological and biochemical changes can be very exast indices of organism intoxication. Chlorophos affects the organism to a lesser extent than chlororganic pesticides. Different species of animals response to the same preparation differently and different pesticides, in their turn, can affect differently one and the same mammal species.